Pemberian Sanksi Pelanggaran Pelaksanaan Jabatan Notaris Dan Perilaku Notaris Oleh Majelsi Pemeriksa - Eka Sulistya (Officium Notarium, 2021)
This study aims to analyze the existence of the Notary Supervisory Board in imposing sanctions for Notaries after the issuance of Ministry of Law and Human Rights Regulation (Permenkumham) No. 15 of 2020 and the implementation of Permenkumham No. 15 of 2020. This is a normative juridical research, namely research whose main basis refers to secondary data consisting of primary, secondary and tertiary legal materials. The results of the study conclude that first, that the Regional Supervisory Council has the authority to impose sanctions on Notaries and Article 77 of the UUJN determines that the Central Supervisory Council has the authority to impose sanctions. However, in Article 1 point 4 of the Permenkumham No. 15 of 2020, it is stipulated that the authority to impose sanctions on Notaries lies with the Examining Council. Permenkumham No. 15 of 2020 contradicts the UUJN and since there are overlapping rules, the Permenkumham should not be able to downgrade or change the provisions in the UUJN. Second, the implementation of Article 1 point 4 of the Permenkumham No. 15 of 2020 on Procedures for Examination of the Supervisory Council Against Notaries is difficult to implement because the higher provisions, namely UUJN, does not regulate or authorize the Examining Council to impose sanctions on Notaries.Key Word: Notary Function, Notary Supervision, sanctioningAbstrakPenelitian ini bertujuan untuk menganalisis keberadaan Majelis Pengawas Notaris dalam pemberian sanksi bagi Notaris pasca terbitnya Permenkumham Nomor 15 Tahun 2020 dan pelaksanaan Permenkumham Nomor 15 Tahun 2020. Penelitian ini adalah penelitian yuridis normatif, yaitu penelitian yang basis utamanya mengacu pada data sekunder yang terdiri dari bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Hasil penelitian menyimpulkan pertama, bahwa Majelis Pengawas Wilayah yang berwenang menjatuhkan sanksi kepada Notaris dan Pasal 77 UUJN menentukan pula Majelis Peng awas Pusat yang berwenang menjatuhkan sanksi. Namun dalam Pasal 1 angka 4 Permenkumham Nomor 15 Tahun 2020 tersebut menentukan bahwa kewenangan pemberian sanksi kepada Notaris ada pada Majelis Pemeriksa. Permenkumham Nomor 15 Tahun 2020 bertentangan dengan UUJN dan terkesan ada tumpang tindih aturan, semestinya Permenkumham tidak bisa men-downgrade atau mengubah ketentuan dalam UUJN. Kedua, pelaksanaan Pasal 1 angka 4 Permenkumham Nomor 15 Tahun 2020 tentang Tata Cara Pemeriksaan Majelis Pengawas Terhadap Notaris sulit diterapkan sebab berdasarkan ketentuan yang lebih tinggi, yakni UUJN tidak mengatur atau memberikan kewenangan terhadap Majelis Pemeriksa untuk memberikan sanksi terhadap NotarisKata Kunci: Jabatan Notaris, Pengawasan Notaris, Pemberian Sanksi